Mapping How Worlds Come to Be - Robert Alexander Gorny (Footprint)
The notion of ‘worlds’ has gained much traction in recent discourses. Across the sciences, humanities and arts, including architecture, studies centring on ‘worlds’ aims to establish a new condition for theorising systems and their wider entanglements. Especially in architecture, there is a plethora of studies that often use a cartographic approach to chart various material (trans)formations of planetary spaces, and/or the wider discourses on spatial practices that may serve as the basis for theorising and practicing towards other possible worlds and futures. In this review I attempt to further these inquiries into spatial production by such ‘other’ means, by calling for a complementary posthuman account in which, following Braidotti, environmental, social, and technological transformations can no longer be understood in isolation. Here, I argue, it is necessary to resume and extend Foucault’s initial call to subsume the formation of built environments (and the various practices that create them) under the general history of technē, here generalised in terms of (cultural) technologies and cosmotechnics. With this aim, the following discusses theoretically-grounded approaches through the spatialisation and coupling of (cosmotechnical) difference.